CuCl-Catalyzed direct C–H alkenylation of benzoxazoles with allyl halides. Issue 35 (29th August 2017) - Li, Die; Wu, Xin-Xing; Gao, Tingyu; Li, Baoguo; Chen, Shufeng
Abstract : An efficient and concise CuCl-catalyzed C2-alkenylation reaction of benzoxazoles with allyl halides has been established. Abstract : An efficient and concise CuCl-catalyzed C2-alkenylation reaction of benzoxazoles with allyl halides has been established. The distinctive features of this protocol include the use of an inexpensive copper salt as a catalyst, simple and readily available starting materials, and ligand-free conditions. An important application of this method to the synthesis of 1, 3-diene substituted benzoxazoles has also been achieved.